Analisis pengaruh store atmosphere, merchandising, promosi, dan pelayanan ritel terhadap Impulse buying pada laris toserba Dan swalayan di klaten - Jayanto, Dwi; , Dra. Wafiatun Mukharomah, MM (2016)
This study aimed to analyze the effect of store atmosphere, merchandise, promotions and services to impulse buying at Laris Supermarkets department stores and Supermarkets in Klaten. This study was quantitative research. This research was conducted in the district of Klaten demgam retrieving objects in one of modern retailing contained in Klaten regency is Laris Department Store and Supermarket. The number of respondents who were taken in this study as many as 150 people. Testing the hypothesis in this study using linear regression analysis with Ordinary Least Square method (OLS). Based on the survey results revealed that atmospherem store merchandising, promotions and retail services significantly influence impulse buying at department stores and Supermarkets Laris customers in Klaten